Disadvantages of Automated Respiratory Gas Exchange Analyzers - Ramos-Álvarez, Juan José; Lorenzo-Capellá, Irma; Calderón-Montero, Francisco Javier (Frontiers in Physiology, 2020)
The use of automated gas exchange analysis systems in exercise studies is common throughout the industrialized world and are frequently used in sports medicine laboratories for the measurement of maximal oxygen uptake (⩒O2 max), as an integrative parameter that allows the physical condition to be assessed, in spite of its limitations. Actually, the fundamental principles behind the measurement of respiratory gas exchange have not changed for a century. It was used a manual Douglas bag method together with separate chemical analyses. The need for faster and more efficient techniques, has conditioned the traditional procedures and determined the emergence of automated systems. However, the validity and reliability of all these different systems is not well known. The common features associates with these systems, also have disadvantages that must be evaluated at the time of the acquisition of an automated equipment: 1) regular quality control checks, which entails other added economic costs, 2) the validity and reliability of the results, which it is necessary to verify and 3) the user does not know the equations that determine the values of oxygen consumption and carbon dioxide production. This work aims to clarify the disadvantages of these automated systems. Not inconsiderable, because after more than a century of use of gas exchange measuring systems, some research laboratories are spurning these automated gas analysis systems and continue to use traditional systems, collecting the exhaled air in Douglas sacks and analyzing the oxygen and carbon dioxide fractions using the Haldane or Scholander apparatus.